Lecturers’ Ability to Support Inclusive Learning To Students With Visual Impairment in Higher Learning Institutions in Tanzania (Tanzania Journal for Population studies and Development, 2023)
The study investigated lecturers’ ability to support inclusive learning to students with visual impairment in higher learning institutions in Tanzania. The study used a qualitative research approach with a multiple case research design. Purposive sampling was used to select 40 participants, including 30 students with visual impairment, 6 lecturers, 2 heads of special needs, and 2 coordinators of a special needs unit. Data were gathered through interviews and focus group discussions and analysed using content analysis. After the analysis, it was found that the majority of lecturers were unable to identify the unique learning needs of students with visual impairment due to the lack of skills and experiences in special needs education. Furthermore, the study found that most lecturers use lecturing as their main teaching method, which does not accommodate students with visual impairment. It was also noted that higher learning institutions lack sufficient supportive teaching and learning materials for students with visual impairment. The study recommends that university curricula be reviewed and modified to accommodate students with special needs and their unique learning needs. Moreover, lecturers and other service providers should be supported with sufficient training in disability and diversity. Lastly, the government should put aside a budget to support students with diverse learning needs to study comfortably in inclusive settings.